2001
DOI: 10.3168/jds.s0022-0302(01)74565-1
|View full text |Cite
|
Sign up to set email alerts
|

Stage of Cycle, Incidence, and Timing of Ovulation, and Pregnancy Rates in Dairy Cattle after Three Timed Breeding Protocols

Abstract: In experiment 1, 705 cows were assigned to three treatments: 1) the Ovsynch protocol (a GnRH injection given 7 d before and another 48 h after one PGF2alpha injection); 2) PGF2alpha + Ovsynch (one PGF2alpha injection given 12 d (d -22) before initiating Ovsynch (d -10); and 3) 2xPG12 (two PGF2alpha injections 12 d apart; d -15 and -3, followed 48 h later by a GnRH injection. All cows were inseminated (d 0) 16 to 20 h after the GnRH injection on d -1. Cyclic status was estimated by serum progesterone. More cows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
98
7
10

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(136 citation statements)
references
References 24 publications
21
98
7
10
Order By: Relevance
“…Therefore, only 82.2% of the cows were synchronised, which agrees with the results of [10,19]. Recently, Cartmill et al [20,21] reported that 83.8% of the cows were cycling in the OVS program, while 5 to 15% of the cows were not cycling at the time of insemination.…”
Section: Discussionsupporting
confidence: 77%
“…Therefore, only 82.2% of the cows were synchronised, which agrees with the results of [10,19]. Recently, Cartmill et al [20,21] reported that 83.8% of the cows were cycling in the OVS program, while 5 to 15% of the cows were not cycling at the time of insemination.…”
Section: Discussionsupporting
confidence: 77%
“…According to Billings and Katz [32], progesterone treatment for as little as 3 days facilitated estrogen-induced receptivity and attractivity of goats during the spring and fall. Corteel et al [13] observed an improved conception rate in anestrous goats treated with CIDR-G and a combination of PGF 2α and eCG.…”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies, this condition was detected with rectal palpation and was estimated to occur in 6 -19% of dairy cows (Kesler & Garverick 1982, Garverick 1997. In recent studies the incidence of anovulation (detected with either blood samples or ultrasonography) in dairy cattle ranged from 18 to 29% (Cartmill et al 2001, Pursley et al 2001, Gü men et al 2003. Follicular cysts can cause economic loss in dairy operations (Youngquist 1986).…”
mentioning
confidence: 99%